Fund Surveillance Over Members of Currency Unions. (Policy Papers; Policy Paper ;, 2005)
Effective Fund surveillance over the members of currency unions entails discussions at the regional level. This requirement derives from the fact that currency union members have devolved responsibility for policy areas that are central to Fund surveillance, notably monetary and exchange rate policies, to regional institutions. Discussions have been held for some time with regional institutions in the euro area, the Central African Economic and Monetary Union (CEMAC), the Eastern Caribbean Currency Union (ECCU), and the West African Economic and Monetary Union (WAEMU). However, only for the EU institutions responsible for euro area policies have these discussions been formalized as constituting an integral part of the Fund's surveillance on the individual members of the currency union. At the conclusion of the 2004 biennial surveillance review, Directors called for formalization of discussions with regional institutions in the remaining currency unions: CEMAC, ECCU and WAEMU. This paper formalize the modalities of discussions with the regional institutions of these currency unions in the context of the Article IV consultations with the members of these currency unions.